Functional outcome of surgical management of degenerative lumbar canal stenosis - Nath, Rajendra (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The long term outcomes of decompressive surgery on relief of pain and disability in degenerative lumbar canal stenosis are unclear. The aim of our study was to evaluate the outcome of surgical management of secondary degenerative lumbar canal stenosis and to analyze the effect on outcome variables using Japanese Orthopaedic Association (JOA) score. MATERIALS AND METHODS: Thirty-two patients of degenerative lumbar canal stenosis managed surgically were included in this study. Laminectomy (n=2), laminectomy with disectomy (n=23), laminectomy and disectomy with instrumental stabilization (n=5), and laminectomy, disectomy with posterior interbody fusion (n=2) were performed. JOA scoring system for low backache was used to assess the patients. The recovery rate was calculated as described by Hirabayashi et al. (1981). Surgical outcome was assessed based on the recovery rate and was classified using a four-grade scale: Excellent, improvement of >90%; good, 75–89% improvement; fair, 50–74% improvement; and poor, below 49% improvement. The patients were evaluated at 3 months, one year and at last followup. RESULTS: At 3-month followup, 18.75% patients showed excellent outcome, 62.50% patients showed good outcome, and 18.75% showed fair outcome. At 1-year followup, 64% patients showed excellent outcome and 36% patients showed good outcome. At >1 year followup (average 34.2 months, range: 2–110 months), 64% patients showed excellent outcome, 28% showed good outcome, and 8% showed fair outcome. No patient had poor outcome. Outcome of the patients improved as the time after surgery increased till 1 year and was sustained thereafter till the last followup. CONCLUSION: Operative treatment in patients of degenerative lumbar canal stenosis yields excellent results as observed on the basis of JOA scoring system. No patient got recurrence of symptoms of nerve compression.